THE ACCOUNTING EXCHANGE. - Littleton, A. C. (The Accounting Review, 1945)
Abstract Public accountants have had a growing conviction for some time that the Certified Public Accountant laws are in need of carefully considered modernization. Now, after extended consideration in committee, the American Institute of Accountants has published a form of bill that state societies will find useful in planning new legislation. If public accounting is to be widely and effectively recognized as a real profession, it has need of statutory recognition of just such aspects as restriction, discipline, education. This will not imply that legislation can create a profession out of an occupation. A profession creates itself. Technical competence comes from study and experience only. The need of the public for technical services arises more from the Complexities of business than out of legislation. And the most effective discipline is self-imposed. Public accountants have created high standards of discipline and have educated themselves to high professional competence. Public accounting in the U.S. has developed until it has come to serve an important public function.